Laser diagnostic methods for plasma sheath potential mapping and electric field measurement - Rath, Jordan L., author; Yalin, Azer P., advisor; Williams, John D., committee member; Rocca, Jorge G., committee member (Colorado State University. Libraries, 2013)
This thesis presents the development of two laser diagnostic approaches for electric field measurements in plasmas and gases. Hall effect thrusters, and other electric propulsion devices, have limited lifetimes due to the erosion of components by ion bombardment of surfaces. A better understanding of the electric field structure in the plasma sheaths near these surfaces would enable researchers to improve thruster designs for extended lifetime and higher efficiency. The present work includes the development of a laser induced fluorescence technique employing a diode laser at 835 nm to measure spatially resolved xenon ion velocity distribution functions (IVDFs) near plasma-surface interfaces (sheaths), from which electric field and spatially-resolved potentials can be determined. The optical setup and demonstrative measurements in a low-density multi-pole plasma source are presented. Also included in this thesis is development of a cavity-enhanced polarimetry technique for electric field measurements in gases via the optical Kerr effect. The high finesse optical cavity allows sensitive measurement of the electric field induced birefringence, improving upon the detection limits of past work using related multi-pass techniques. Experimental results are presented for carbon dioxide, nitrogen, oxygen and air along with comparisons to model predictions based on published Kerr constants.
Keywords: sheath; optics; polarimetry; plasma; Hall thruster; laser induced fluorescence